Acupuncture for Chemotherapy‐Induced Peripheral Neuropathy in Breast Cancer Survivors: A Randomized Controlled Pilot Trial. (14th October 2019) - Lu, Weidong; Giobbie‐Hurder, Anita; Freedman, Rachel A.; Shin, Im Hee; Lin, Nancy U.; Partridge, Ann H.; Rosenthal, David S.; Ligibel, Jennifer A.
Abstract: Background: Chemotherapy‐induced peripheral neuropathy (CIPN) is one of the most debilitating long‐term side effects in breast cancer survivors. We conducted a randomized controlled pilot trial to assess the feasibility, safety, and effects of an acupuncture intervention on CIPN in this population. Patients and Methods: Women with stage I–III breast cancer with grade 1 or higher CIPN after taxane‐containing adjuvant chemotherapy were randomized 1:1 to an immediate acupuncture (IA) arm or to a waitlist control group (CG). Participants in the IA arm received 18 sessions of acupuncture over 8 weeks, then received no additional acupuncture. Patients in the CG arm received usual care over 8 weeks, followed by nine sessions of acupuncture over 8 weeks. Measures including Patient Neurotoxicity Questionnaire (PNQ), Functional Assessment of Cancer Therapy—Neurotoxicity subscale (FACT‐NTX), and Brief Pain Inventory—short form (BPI‐SF) were collected at baseline and at 4, 8, and 16 weeks after enrollment. Results: Forty women (median age, 54) were enrolled (20 to IA and 20 to CG), with median time between completion of chemotherapy and enrollment of 14 months (range 1–92). At 8 weeks, participants in the IA arm experienced significant improvements in PNQ sensory score (−1.0 ± 0.9 vs. −0.3 ± 0.6; p = .01), FACT‐NTX summary score (8.7 ± 8.9 vs. 1.2 ± 5.4; p = .002), and BPI‐SF pain severity score (−1.1 ± 1.7 vs. 0.3 ± 1.5; p = .03), compared with those in the CG arm. No serious side effects were observed. Conclusion: Women with CIPN after adjuvant taxane therapy for breast cancer experienced significant improvements in neuropathic symptoms from an 8‐week acupuncture treatment regimen. Additional larger studies are needed to confirm these findings. Implications for Practice: Chemotherapy‐induced peripheral neuropathy (CIPN) is a toxicity that often persists for months to years after the completion of adjuvant chemotherapy for early breast cancer. In a randomized pilot trial of 40 breast cancer survivors with CIPN, an 8‐week acupuncture intervention (vs. usual care) led to a statistically and clinically significant improvement in subjective sensory symptoms including neuropathic pain and paresthesia. Given the lack of effective therapies and established safety profile of acupuncture, clinicians may consider acupuncture as a treatment option for mild to moderate CIPN in practice. Abstract : Chemotherapy‐induced peripheral neuropathy (CIPN) is a common side effect of chemotherapy. This article describes results of a study that evaluated the feasibility and benefits of acupuncture in breast cancer survivors with CIPN symptoms.